Synthesis of micro-crystals of transparent cobalt aluminate, shrouded in siliceous material, from Co(II)-exchanged zeolite X - Lodge, M; Edwards, P; Anderson, P; Jones, M; Gameson, I (2006)
We report an investigation of the synthesis of a cobalt aluminate spinel composite from the heat-induced collapse of cobalt ion-exchanged sodium zeolite X. The work presented here adds to earlier studies by illustrating that by careful control of synthesis and reaction conditions, both the phase composition and crystallite size of the spinel can be controlled. The spinel crystallites grow within siliceous materials formed by the collapse of the zeolite framework, with the crystalline particles being completly shrouded by the siliceous matrix. © 2005 Elsevier Ltd. All rights reserved.